Hybrid purity assessment of safflower (Carthamus tinctorius L.) F1 s using inter-simple sequence repeats (ISSRs): HYBRID PURITY ASSESSMENT OF SAFFLOWER F1 s USING INTER-SIMPLE SEQUENCE REPEATS - NIRMALA BHARTI PATEL; RAJEEV SHRIVASTAVA (Journal of Oilseeds Research, 2016)
Twelve hybrids were developed using four lines and three testers parents of safflower. Genetic purity of these twelve safflower hybrids was tested using 7 ISSR primers which showed polymorphism between parents. ISSR primers UBC 807, UBC 812, UBC 815, UBC 834, UBC 840, UBC 841 and UBC 842 could differentiate parents and identify true hybrids in 2,4,1,1,1,2, and 2 crosses, respectively. Hybrid seed production in safflower is a challenge due to easy selfing of female parents and thus degrades the quality of seed lot. These ISSR primers can be used to test the hybrid purity in hybrid seed production.